The structure of industry protection in Mexico: 1960-1980 - Ulrich Lächler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1986)
In the 1950s, Mexico and a number of other Latin American countries opted for a strategy of inward-oriented development aimed at accelerating the pace of industrialization. This strategy relied heavily on a process of import substitution brought about by creating a protected domestic environment biased in favor of the modern manufacturing sectors. By the early 1960s, it was already becoming clear to many observers that import substitution policies were not delivering all they had promised, but rather provided a hindrance to development (Hirschman, 1968). Nevertheless, Mexico continued to pursue a highly protectionist course in subsequent years; see Balassa (1983).
Keywords: 330; Protektionismus; Erziehungszoll; Mexiko